Digital Governance in Archipelagic Villages: Local Government Innovation in Enhancing the Effectiveness of Village Governance - Muksin, Isra; Nurdin, Anbiya N; Wahid, Safitri; Dasim, Nurlaili (Pt. Anagata Sembagi Education, 2026)
This study examines digital governance in archipelagic villages as a strategic approach to improving governance effectiveness amid challenges of limited access, infrastructure, and institutional capacity. Digital governance is expected to accelerate administrative services, enhance transparency, and strengthen citizen participation, yet its implementation often faces constraints related to digital infrastructure, literacy, and organizational readiness. This research employs a qualitative approach with a descriptive-analytical design, utilizing secondary data obtained through a systematic literature review of reputable academic journals and policy documents. Data were collected through documentation techniques and analyzed using qualitative content analysis and comparative methods to identify patterns of digital innovation and their impacts on governance effectiveness. The results indicate that digital governance innovations such as village administrative applications, integrated service systems, digital financial management platforms, and SPBE-based village websites significantly improve service efficiency, transparency, accountability, and citizen participation. However, these benefits are not evenly realized due to persistent challenges, including limited ICT infrastructure, low digital literacy, and weak institutional capacity. The study concludes that the effectiveness of digital governance in archipelagic villages depends on an integrated and adaptive approach that combines technological innovation with infrastructure development, capacity building, and multi-stakeholder collaboration to ensure sustainable and inclusive governance transformation